Echocardiography in prehospital emergency medical service: Experience of Institute for Emergency Medicine Novi Sad - Vengrin Aleksandar; Đurđev Nemanja (ABC: časopis urgentne medicine, 2015)
INTODUCTION: The portable ultrasound devices allow EMS doctors to perform echocardiography in a prehospital setting, in ambulance cars and on the spot of an accident. Due to the time and technical limitations, ECHO scan is focused on the quick assessment of the cardiac parameters, its anatomical relations, myocardial contractivity and segmental kinetics and valvular functionality. AIM: Aim of the study: to determine the significance of echocardiography in diagnostics and treatment of the emergent patients. MATERIALS AND METHODS: Doctors of Institute for Emergency Medicine Novi Sad, trained in echosonography, performed 53 ECHO scans between April and November 2014. Indications for echocardiography included chest pain with non-diagnostic ECG, dispnea and transient loss of consciousness / syncope. RESULTS: Most common ECHO findings included valvular abnormalities/disfunctionalities, abnormal myocardial kinetics (segmental hypokinetics and akinetics), left ventricular hypertrophy, pericardial effusion and right ventricular abnormalities. CONCLUSION: Echocardiography in everyday practice of EMS has a great significance, determining evaluation and further treatment of certain types of critical patients. We find it necessary that each doctor working in EMS should be trained to apply this diagnostic method.